Upgrading Students’ Writing Performance through Contextual Teaching and Learning Approach - Hafirah Patang; Iski Sulastri (Ethical Lingua: Journal of Language Teaching and Literature, 2015)
This is a pre-experimental research using one group pre-test and pos-test design, which aims at finding out the effects of Contextual Teaching and Learning approach in improving students’ ability in writing descriptive text at the eleventh grade students of SMA Negeri 1 Sabbang. The population of this research is the eleventh grade students of SMA Negeri 1 Sabbang. The total number of the population is 149 of the all eleventh students. The researcher took 20 students as the sample from one class by using cluster sampling technique. This research employed writing test as the instrument of data collection. The result of this test is used to assess to what extent Contextual Teaching and Learning approach can improve the students’ ability in writing descriptive text. After several meetings, this research found out that the use of Contextual Teaching and Learning approach is significantly effective to improve the students’ ability in writing descriptive text. It is supported by looking at the mean score obtained by students through pre-test is 51.55 and post-test is 76.86.